More Than a Tick Box: Medical Checklist Development, Design, and Use. (January 2018) - Burian, Barbara K.; Clebone, Anna; Dismukes, Key; Ruskin, Keith J.
Abstract : Despite improving patient safety in some perioperative settings, some checklists are not living up to their potential and complaints of "checklist fatigue" and outright rejection of checklists are growing. Problems reported often concern human factors: poor design, inadequate introduction and training, duplication with other safety checks, poor integration with existing workflow, and cultural barriers. Each medical setting—such as an operating room or a critical care unit—and different clinical needs—such as a shift handover or critical event response—require a different checklist design. One size will not fit all, and checklists must be built around the structure of medical teams and the flow of their work in those settings. Useful guidance can be found in the literature; however, to date, no integrated and comprehensive framework exists to guide development and design of checklists to be effective and harmonious with the flow of medical and perioperative tasks. We propose such a framework organized around the 5 stages of the checklist life cycle: (1) conception, (2) determination of content and design, (3) testing and validation, (4) induction, training, and implementation, and (5) ongoing evaluation, revision, and possible retirement. We also illustrate one way in which the design of checklists can better match user needs in specific perioperative settings (in this case, the operating room during critical events). Medical checklists will only live up to their potential to improve the quality of patient care if their development is improved and their designs are tailored to the specific needs of the users and the environments in which they are used. Abstract : Published ahead of print July 28, 2017.